THE EFFECT OF APPLIED FINANCIAL TECHNOLOGY PRODUCTS (FTPs) ON FINANCIAL PERFORMANCE: CASE OF SHARIA BANKING IN INDONESIA 2017-2021 - Ilma Nurlela; Estu Estu Widarwati (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2024)
Banking is an institution that has a role to carry out the intermediary function of the flow of funds in an economy. Proper business digitization in the Islamic banking and finance sector is a must that will lead to achieving growth in the Islamic finance market share. The financial technology system can help the financing process become faster and more measurable by mitigating risks that can be done early on. Based on this, it is an opportunity for Islamic banking to use financial technology. The purpose of this study is to examine the effect of applied financial technology products on financial performance. This study uses a sample of Islamic banks registered in the OJK for the period 2017-2021. The sample selection method used in this research is purposive sampling. Hypothesis testing used in this research using panel data regression analysis. The method used in this research is a descriptive verification method using a quantitative approach. Hypothesis testing using the Eviews9 application. The results show that financial technology products have an effect on financial performance proxied by ROA and financial technology products have no effect on financial performance proxied by BOPO, CAR, FDR, ROA. It is expected that Islamic banks will make adjustments and improve the application of financial technology products so that it can improve banking performance. In addition, to promote banking products to the general public so that people are interested in investing and applying Islamic banking products.